2018
DOI: 10.1016/j.oceaneng.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of skirted foundations in sand-over-clay under combined V-H-M loading

Abstract: Circular skirted foundations are used widely in the offshore oil and gas industry and renewable energy industry to support subsea infrastructure and founding turbines. The foundations are subjected to combined vertical-horizontal-moment (V-H-M) loadings during operation. This paper describes an extensive investigation of the response of installed circular skirted foundations under operational loadings in sand-over-clay. The overarching aim was to examine the influence of the presence of a sand layer on the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The sand was modelled as an elastic-perfect plastic material in accordance with the Mohr-Coulomb yield criterion. The unit weight of soil is considered as γ = 19.5 KN/m3 [4] and the under watered elastic properties having a 50 MPa young's modulus and the poisons ratio Ʋ of 0.3 [9]. The undrained plastic properties like cohesion c, internal friction angle Ø and dilation angle Ψ are attributed to the sand.…”
Section: Finite Element Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sand was modelled as an elastic-perfect plastic material in accordance with the Mohr-Coulomb yield criterion. The unit weight of soil is considered as γ = 19.5 KN/m3 [4] and the under watered elastic properties having a 50 MPa young's modulus and the poisons ratio Ʋ of 0.3 [9]. The undrained plastic properties like cohesion c, internal friction angle Ø and dilation angle Ψ are attributed to the sand.…”
Section: Finite Element Modelsmentioning
confidence: 99%
“…The analysis of vertical load carrying capacity of skirt foundations are being tested over a period of time [5], [6]. The capacity of piles in various soil densities is assessed using both experimental [7] and numerical modelling [8] with varying in aspect ratios (L/D) [9] and the failure envelops were also considered for all spacing impacts [10]. Coming to field tests outcomes with skirt bucket type foundation in sand with vertical loading are shown in [4], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Sand-overlying-clay soil deposit is a complex, but commonly encountered, soil profile in petroleum regions and offshore wind farms, for example, in the Yellow Sea of Korea, North Sea, Gulf of Mexico, South China Sea, offshore India and Thailand [18,19].…”
Section: Introduction 1conceptmentioning
confidence: 99%
“…Existing understandings only cover the failure mechanisms of conventional types of foundations in such sand-overlying-clay soil profiles [18][19][20][21][22]. For example, Zheng et al (2018) [23] found a 'punch-through' failure pattern for strip footings in the sand-over-clay layered deposits, where the upper sand block is pushed into the underlying clay due to the vertical compression under V-H-M combined loadings.…”
Section: Introduction 1conceptmentioning
confidence: 99%
“…It is therefore important to distinguish between the behavior of embedded and skirted foundations. While investigation of bearing capacity of shallow foundations has typically considered fully solid concepts (e.g., Salgado et al, 2004 andGourvenec, 2008), the bearing behavior, failure mechanisms, and stiffness of skirted foundation have received considerable attention recently (Yun and Bransby, 2007;Mana et al, 2012;Liu et al, 2017;Wang et al, 2017;Jalbi et al, 2018;and Zou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%